Remembering Guru Nanak: Articulations of Faith and Ethics by Sikh Activists in Post 9/11 America - Sangeeta Kaur Luthra (Religions, 2021)
This paper explores the role of activism as an inflection point for engagement with religious and cultural identity by younger generations of Sikhs in the US. The response of young Sikh activists and the effects on the community are examined in the context of the 11 September 2001 terrorist attacks in the US. The paper begins with the reflections of a Sikh activist about her personal journey learning about Sikh faith and history, and her activism and personal interests. Important themes that reflect the attitudes of contemporary Sikh activists and organizations are discussed. The effects of the post-9/11 backlash against Sikhs in the US are compared to Guru Nanak’s experiences of and response to violence, strife, and injustice. The social, psychological, and spiritual benefits of service for those who provide service and care are explored in relation to Sikh philosophy, and from the point of view of contemporary cultural and historical studies of Sikh seva (selfless service) and humanitarianism. The paper concludes that many Sikhs, particularly those coming of age in the late 20th and early 21st century, often referred to as millennial and Generation Z, view social justice activism, humanitarianism and Sikh seva as central and equal to other pillars of Sikhism like worship and devotional practices.